Rice ETHYLENE RESPONSE FACTOR 101 Promotes Leaf Senescence Through Jasmonic Acid-Mediated Regulation of OsNAP and OsMYC2 - Lim, Chaemyeong; Kang, Kiyoon; Shim, Yejin; Sakuraba, Yasuhito; An, Gynheung; Paek, Nam-Chon (Frontiers in Plant Science, 2020)
Leaf senescence is the final stage of leaf development and an important step that relocates nutrients for grain filling in cereal crops. Senescence occurs in an age-dependent manner and under unfavorable environmental conditions such as deep shade, water deficit, and high salinity stresses. Although many transcription factors that modulate leaf senescence have been identified, the mechanisms that regulate leaf senescence in response to environmental conditions remain elusive. Here, we show that rice (Oryza sativa) ETHYLENE RESPONSE FACTOR 101 (OsERF101) promotes the onset and progression of leaf senescence. OsERF101 encodes a predicted transcription factor and OsERF101 transcript levels rapidly increased in rice leaves during dark-induced senescence (DIS), indicating that OsERF101 is a senescence-associated transcription factor. Compared with wild type, the oserf101 T-DNA knockout mutant showed delayed leaf yellowing and higher chlorophyll contents during DIS and natural senescence. Consistent with its delayed-yellowing phenotype, the oserf101 mutant exhibited downregulation of genes involved in chlorophyll degradation, including rice NAM, ATAF1/2, and CUC2 (OsNAP), STAY-GREEN (SGR), NON-YELLOW COLORING 1 (NYC1), and NYC3 during DIS. After methyl jasmonate treatment to induce rapid leaf de-greening, the oserf101 leaves retained more chlorophyll compared with wild type, indicating that OsERF101 is involved in promoting jasmonic acid (JA)-induced leaf senescence. Consistent with the involvement of JA, 2 the expression of the JA signaling genes OsMYC2/JA INSENSITIVE 1 (OsJAI1) and CORONATINE INSENSITIVE 1a (OsCOI1a), was downregulated in the oserf101 leaves during DIS. Transient transactivation and chromatin immunoprecipitation assays revealed that OsERF101 directly binds to the promoter regions of OsNAP and OsMYC2, which activate genes involved in chlorophyll degradation and JA signaling-mediated leaf senescence. These results demonstrate that OsERF101 promotes the onset and progression of leaf senescence through a JA-mediated signaling pathway.